What do criteria and indicators assess?: an analysis of five C&I sets relevant for forest management in the Brazilian Amazon - Pokorny, B.; Adams, M. (2003)
The diversity of C&I sets is often a cause for uncertainty and confusion, and probably one of the reasons for the still unsatisfactory acceptance of C&I as a support for implementation of sustainable forest management so far. In order to halt this erosion of confidence in C&I the presented paper evaluated the diversity of five C&I sets (CIFOR, ACM, FSC, ITTO and Tarapoto) relevant for the Brazilian Amazon by analyzing frequencies of C&I in relation to parameters about content and quality. The study demonstrated that the C&I sets, although addressing the social, technical, ecological and economic dimensions of sustainability, show different thematic focus. A general lack of validity was attested as well as missing specificity and practicability of the indicators. To increase objectivity and transparency, the C&I have to more clearly and unambiguously reflect what is really assessed. It is recommended to include the discussion about verifiers and assessment methods in the development of C&I sets. To avoid misunderstandings and to open to possibility for less complex more practicable C&I sets, we recommend to constrict the objective of the assessment more clearly, considering the potential clients and frame-conditions for its application.